Autoimmunity related to anti-Nax and anti-ZSCAN1 autoantibodies in adipsic hypernatremia - Akari Nakamura-Utsunomiya (Endocrine Journal, 2024)
“Adipsic hypernatremia” is clinically characterized by chronic elevation of plasma [Na+] with an inappropriate lack of thirst and upward resetting of the osmotic set point for arginine vasopressin (AVP) secretion, combined with a relative deficiency of AVP, thereby resulting in persistent hypernatremia. Many cases are accompanied by structural lesions in the hypothalamus, pituitary gland, and circumventricular organs (CVOs). On the other hand, cases without structural lesions have been reported since the 1970s, but the pathophysiology was unknown for a long time. In 2010, Hiyama et al. reported that an anti-Nax antibody response caused adipsic hypernatremia in a pediatric case with ganglioblastoma. In recent years, advances in clinical research have led researchers to recognize that an autoimmunological pathogenic mechanism might be associated with periventricular organs such as the subfornical organ (SFO). In addition, in pediatric cases diagnosed as ROHHAD (rapid-onset obesity with hypoventilation, hypothalamic dysfunction, autonomic dysregulation) syndrome, it has been reported that half of the cases have abnormal serum Na levels, and some research findings indicated an autoimmune mechanism acting on the organs of the hypothalamus and CVOs. Then, anti-ZSCAN1 antibody response was detected in cases diagnosed as ROHHAD-NET in 2022. In this review, by summarizing a series of studies on Nax and ZSCAN1, which are expressed in the hypothalamus, pituitary gland, and SFO, I would like to describe the current findings of the autoimmune pathogenesis of adipsic hypernatremia.